Pendampingan Pengelolaan Sampah Berbasis Ekonomi Sirkular Perspektif Maqāṣid al-Syarī‘ah pada Masyarakat Desa Hegarmanah, Jatinangor, Sumedang - Moch. Hoerul Gunawan; Irni Sri Cahyanti; Mohammad Yahdi; Ninda Annisa Mufida Pertiwi; Aghni Aulia Aziz; M. Syafrie Ramadhan; Neneng Wahyuni; Naila Sri Sukma Ayu; Nia Kurnia Lestari; Muhammad Izzul Syahmi Zulkepli (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
Waste management at the community level remains a multidimensional challenge affecting environmental quality, public health, and socio-economic welfare. This community service program aims to implement and analyze circular economy–based waste management integrated with the values of maqāṣid al-sharī‘ah at TPS Sauyunan Hegarmanah, Jatinangor District, Sumedang Regency. The program employed a Participatory Action Research (PAR) approach, actively involving waste management officers, local residents, environmental volunteers, and community leaders throughout all stages, including problem identification, action planning, implementation, observation, and collective reflection. The results indicate that the application of waste segregation, recycling, and reuse practices effectively reduced residual waste volume, increased the economic value of waste, and enhanced community participation and behavioral change. The integration of circular economy principles with the maqāṣid al-sharī‘ah framework strengthened the dimension of public benefit (maṣlaḥah), as reflected in the protection of life (ḥifẓ al-nafs) through a cleaner and healthier environment, the protection of wealth (ḥifẓ al-māl) through improved economic value and resource efficiency, and the protection of the environment (ḥifẓ al-bī’ah) through sustainable waste management practices. This program demonstrates that a community-based approach grounded in Islamic values is effective in promoting sustainable and socially meaningful waste management.